Changes in Gambling Behavior during the COVID-19 Pandemic—A Web Survey Study in Sweden - Håkansson, Anders (Int J Environ Res Public Health, 2020)
The COVID-19 pandemic has dramatically changed everyday life, and policy makers have raised concerns about possible changes in gambling patterns during the pandemic. This study aimed to examine whether self-reported gambling has increased during the pandemic, and to examine potential correlates of such a change. This general population survey study in Sweden collected self-report data from 2016 web survey members (51 percent men, nine percent moderate-risk/problem gamblers). Correlates of increased gambling and increased gambling specifically due to COVID-19-related cancellation of sports were calculated. Four percent reported an overall gambling increase during the pandemic. The proportion of individuals reporting an increase, compared to individuals reporting a decrease, was markedly higher for online casinos (0.62), online horse betting (0.76) and online lotteries (0.73), and lower for sports betting (0.11). Overall, gambling increases were independently associated with gambling problems and increased alcohol consumption. In the sub-group, where there was an increase in specific gambling types in response to cancelled sports betting events, rates of gambling problems were high. In conclusion, only a minority report increased gambling in response to the pandemic, but this group has markedly higher gambling problems and changes in alcohol consumption, and may represent a sub-group with a particularly high vulnerability. This calls for preventive action in people with higher gambling risks in response to the pandemic.